Comparable Long-Term Outcomes of Cyclosporine and Infliximab in Patients With Steroid-Refractory Acute Severe Ulcerative Colitis: A Meta-Analysis - Szemes, Kata; Soós, Alexandra; Hegyi, Péter; Farkas, Nelli; Erős, Adrienn; Erőss, Bálint; Mezősi, Emese; Szakács, Zsolt; Márta, Katalin; Sarlós, Patrícia (Frontiers in Medicine, 2020)
Background: In steroid-refractory acute severe ulcerative colitis (ASUC), cyclosporine (CYS) or infliximab (IFX) may be considered as a second-line alternative to avoid colectomy. There are short-term data reported, but until now, there is no meta-analysis regarding long-term outcomes of CYS and IFX in patients with ASUC. Aim: To compare long-term efficacy and safety of CYS and IFX in a meta-analysis. Methods: Three electronic databases (PubMed, Embase, Cochrane Central Register of Controlled Trials) were searched for studies which compared CYS vs. IFX in adults with ASUC. Long-term colectomy-free rate from 1 to 10 years during CYS or IFX therapy was collected, last updated up to 22nd May 2019. Primary outcome was long-term colectomy-free rate, secondary outcomes were adverse events (AE), serious adverse events (SAE), and mortality. Long-term colectomy-free survival and safety measures were pooled with the random-effect model. Odds ratios (OR) with 95% confidence intervals (CI) were calculated. Results: Data from 1,607 patients in 15 trials were extracted. In the first 3 years, pooled OR for colectomy-free survival was higher with IFX than with CYS (OR = 1.59, 95% CI: 1.11–2.29, p = 0.012; OR = 1.57, 95% CI: 1.14–2.18, p = 0.006; and OR = 1.75, 95% CI: 1.08–2.84, p = 0.024; at 1, 2, and 3 years, respectively). However, the significant difference remained undetected from the fourth year of follow-up and in subgroup of RCTs (OR = 1.35, 95% CI: 0.90–2.01, p = 0.143; OR = 1.41, 95% CI: 0.94–2.12, p = 0.096; and OR = 1.34, 95% CI: 0.89–2.00, p = 0.157; at 1, 2, and 3 years, respectively). No significant difference was detected regarding adverse events, serious adverse events and mortality between the groups. The neutral associations proved to be underpowered with trial sequential analysis. Conclusion: However observational studies show IFX as a better choice, according to the RCTs, choosing either CYS or IFX as rescue therapy for ASUC, the long-term outcomes are not different, although further large RCTs are warranted.